Information-sharing in health and social care: Lessons from a socio-technical initiative. Issue 5 (4th July 2019) - Shah, Tejal; Wilson, Louise; Booth, Nick; Butters, Olly; McDonald, Joe; Common, Kathryn; Martin, Mike; Minion, Joel; Burton, Paul; Murtagh, Madeleine
ABSTRACT: Advances in information technology have led to new and innovative approaches in data-sharing, analysis, interpretation, and the potential for real-time responses to changes in health and social care status. However, health and social care information is not only complex but often socially and personally sensitive in ways that do not apply in other domains. This requires adoption of a tailored interdisciplinary (social, ethical, legal, technical and data science) and intersectoral (health and social care, academic and commercial institutions and citizens) approach to technology development. The authors present some important lessons to date from ongoing development of an innovative infrastructure for sharing health and social care data. IMPACT: Data is essential for delivering direct care, service planning and improvement, and research ethically, lawfully, safely and efficiently. The article exemplifies, with the help of a region-wide health and social care information-sharing initiative, the importance and need for strategic planning and collaborative decision-making within each of these dimensions. It thus contributes to improved understanding of the scope, opportunities, benefits, limitations and practicalities of information-sharing in health and social care. The article is therefore relevant for all stakeholders, including patients, practitioners from across care settings, commissioners, managers, technologists, academics, innovators, designers and governance teams.